Proses Afiksasi Yang Memengaruhi Pemertahanan Bahasa Bali Melalui Gending Rare Pada Anak-Anak Di Sanggar Kukuruyuk - Permana Mahardika, I Putu (Humanis; Volume 15. No.2. Mei 2016)
Research of Balinese maintenance on gending rare in Sanggar Kukuruyuk has the goal to describe the efforts of Balinese maintenance . Gending rare of a Balinese is one of the means of an effictive communication in the development of the Balinese in early years and to describe affixes on gending rare taught in Sanggar Kukuruyuk. The theory used is sociolinguistic in sub theory shift and maintenance language . The study was conducted by using method sand techniques that are divided into three stages: (1) stage of the supply data used observation and interview methods accompanied by fishing techniques, recording techniques, and notes techniques. (2) stage of the data analysis used quantitative and qualitative methods, accompanied by the element directly immediate constituent analysis (BUL) techniques by Sudaryanto. (3) stage of the presentation analysis results used formal and informal methods, accompanied by inductive and deductive techniques. The result obtained research of Balinese maintenance on gending rare in Sanggar Kukuruyuk are used affixes easily understandable by childern. The affixes forms are prefixes, sufixes, konfixes, . Prefixes used are {ma-} /m?-/ and N-. Sufixes used are {-in} , {-e} , {-ne} , {-ang} , konfixes used is {ma- / -an}, and other affixes used are prefixes N- and sufixes {-ang}, prefixes N- and sufixes {-in}, prefixes N- and sufixes {-an} . Affixation in the gending rare samples mostly classified by verb or affixation which form the verb words class. Simply affixes used on gending rare, causing children is able to understand intentions contained on gending rare samples. To understand the meaning contained on gending rare samples, children in Sanggar Kukuruyuk can add Balinese vocabulary.
Keywords: gending rare, afifixes, balinese maintenance